INEQUALITY IN CITIES An analysis of income distributions and spatial patterns in American and European metropolitan areas - Lukavec, Martin, 1980-; Toth, Petr, 1962-; Čadil, Jan; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This dissertation offers a comprehensive examination of inequality in metropolitan areas, shown in case studies from Europe and the United States. It investigates the urban/rural divide in European Union regions, finding that the level of disposable income is positively influenced by the degree of urbanization. It also finds a positive impact of urbanization on life expectancy. This highlights the divide between urban and rural regions with respect to both the standard of living and average life span.In an analysis of income distribution in the 20 largest metropolitan areas in the United States for the years 2012 and 2017, I found that inequality can result from various aspects of the income distribution and its shape. I also found a number of interesting interlinkages, including, for example, that skewness is likely to move in unison with the coefficient of variation. I also found that mean income negatively influences both skewness and the coefficient of variation. Wealthier metropolitan areas are likely to display both a smaller skewness of income distribution and lower relative dispersion, and can be considered more equal.Additionally, I have found that the spatial mismatch of households, defined as the spatial misallocation of households by income in relation to the location of jobs, is influenced by the overall level of inequality. Higher-income households are more likely to locate closer to central business areas in metropolitan areas with a lower GINI index. The scope of spatial mismatch varies greatly between metropolitan regions, as does its trend between 2012 and 2017. During this period, spatial mismatch decreased statistically significantly in 3 metropolitan areas and did not increase in any
Vedoucí práce: Petr Toth
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: regionalistika - veřejná správa [obor disert. práce]; disertace; dissertations